PENILAIAN POTENSI EKOWISATA RIAM PANGAR DI KABUPATEN BENGKAYANG - Rianti, Reny; Arum Pynanjung, Pramushinta (JURNAL BORNEO AKCAYA, 2017)
Bengkayang Regency is an area which rich in natural resources. If its are properly managed, they will support sustainable regional development, especially to support regional tourism and nature conservation. Riam Pangar is one object of natural wealth that has the charm of ecotourism in Bengkayang. The study aims to determine the potential of Riam Pangar as a potential ecotourism in Bengkayang Regency. This research is conducted quantitatively by analyzing the Riam Pangar’s internal factor of attraction. This study also analyzes external factors including its ecotourism management agencies and ancillary services. Assessment of tourism potential is based on the Guidelines for the Assessment of PHKA Nature Attraction in 1993 and 2003. The results of the research inform that Riam Pangar Bengkayang Regency is one of priority ecotourism destinations in 2016. Appraisal of attraction potential of Riam Pangar by society and tourists shows the classification of medium potency (B) with value 1089. Local Government assessed that the potential attraction at the place is high (A) with a value of 1410. Tourist ratings show information about Riam Pangar’s attraction is not known by the visitor. Beside, many potential attractions have not yet been explored by the Manager or Local Government. This is an input to the Disparekraf and Nature Tourism Manager in Bengkayang Regency to further explore and promote the potential attractions of the natural attractions. Potential supporting facilities and infrastructure is still low, as well as the availability of clean water is still difficult to obtain. Social conditions is supported by Kelompok sadar Wisata (Pokdarwis). It should be nurtured sustainably by Local Government to improve the quality of service to tourists. The result is expected to become information and recommendation to Government of Bengkayang Regency in determining alternative of policy planning and determine the right strategy to develop Riam Pangar management in Bengkayang Regency